Mytologen Grundtvig - Elbek, Jørgen (Grundtvig-studier, 1983)
Grundtvig the Mythologist By Jørgen Elbek The aim of this paper is to present Grundtvig’s lifelong work on Norse and Greek mythology as an attempt to illuminate intellectual and spiritual structures that elude direct description since they cannot be viewed from outside.In the light of a survey of the various trinitarian formulations which in the European tradition have been employed to denote the basic capacities of the human psyche the paper shows how Grundtvig succeeds in drawing firm lines to connect on the one hand reason, imagination and feeling (in his poetics: light energy and heat), and on the other hand the two sets of ruling gods: Odin, Tyr and Thor and Hades, Zeus and Poseidon, in addition to the cosmic elements that they represent: earth, air and water.Particular emphasis is laid upon Grundtvig’s dream of a cultural renewal in the form of a three-way mythological marriage, in which the higher psychical abilities could mate with the lower instincts and raise them to their own level, by which process the former would draw life-energy and the latter gain clarity.